Understanding hazards, consequences, LOPA, SILs, PFD, and RRFs as related to risk and hazard assessment. Issue 3 (25th July 2014) - Blanco, Roberto Fernández
<x xml:space="preserve">Abstract</x> This article is intended for any engineer, supervisor, or manager who does not specialize in process safety engineering. It presents the concept of layers of protection analysis, safety integrity level (SIL) and its relationship to probability of failure on demand (PFD) and the related risk reduction factors (RRFs). Novel SIL/PFD/RRF graphics are presented to help the reader understand the concepts involved. An example using a safety instrument function for a gas‐fired boiler is also used to help the reader understand the concepts. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 208–216, 2014